(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3GdSjf hGdJGA hGdQGA (B: (3SJQ GdTF jSJQg SJQkG CNaGg hbhdg JYGdi (B( (3LYdfG Hjfc hHjf GdPjf dGjDefhf HGdBNQI MLGHkG eSJhQkG (B) s
(3BNQgG (B:s
(3GdWGA hGdeje hGdjGA Wei GdHjJ eGd hYdG ebdhHg eGW Yfi ejWkG hejGWkG hCeGW JfNi hHYO heGWg Yfi hCeGWg fMGg hOaYg hJeGjW Gdbhe JHGYOhG haSO eG Hjfge GdMeO ddg s
(3GdfSNI GdKGfjI YTQIs
(3HgG fXGe GdJYbjHIs
(3cJHJ SfI (B281s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B214 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs